2016
DOI: 10.1002/hon.2375
|View full text |Cite
|
Sign up to set email alerts
|

PD1 and PDL1 expression in primary central nervous system diffuse large B‐cell lymphoma are frequent and expression of PD1 predicts poor survival

Abstract: Primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) is a rare and aggressive type of diffuse large B-cell lymphoma (DLBCL) whit poorly understood pathogenesis. Finding biomarkers associated with patient survival may be important for understanding its physiopathology and to develop new therapeutic approaches. We investigated 32 PCNS-DLBCL from immunocompetent patients for BCL2, CMYC, LMO2, and P53 expression and for cytogenetic aberrations of BCL2, BCL6, and MYC genes, all known for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
3
33
1
Order By: Relevance
“…In previous studies of PCNS-DLBCL, high PD-L1 expression was unrelated, 21 or related to a favorable prognosis; 20,22 an increased PD-1 + TILs were related to an unfavorable prognosis. 20,21 This study included the largest population of any similar work to date, analyzed the prognostic implications in experimental and validation groups and according to treatment modality, involved a multivariate analysis, quantified PD-L1 expression and enumerated TILs, and evaluated PD-L1 expression together with CD8 + or PD-1 + TILs. We found that tumoral PD-L1 expression was an independent prognostic indicator of a poor OS.…”
Section: Pd-1 Expression Is Induced By T-cell Receptor Signaling On Amentioning
confidence: 82%
See 1 more Smart Citation
“…In previous studies of PCNS-DLBCL, high PD-L1 expression was unrelated, 21 or related to a favorable prognosis; 20,22 an increased PD-1 + TILs were related to an unfavorable prognosis. 20,21 This study included the largest population of any similar work to date, analyzed the prognostic implications in experimental and validation groups and according to treatment modality, involved a multivariate analysis, quantified PD-L1 expression and enumerated TILs, and evaluated PD-L1 expression together with CD8 + or PD-1 + TILs. We found that tumoral PD-L1 expression was an independent prognostic indicator of a poor OS.…”
Section: Pd-1 Expression Is Induced By T-cell Receptor Signaling On Amentioning
confidence: 82%
“…The few previous studies to address this issue used small sample numbers and yielded conflicting results. [19][20][21][22] Thus, we investigated PD-L1 expression and the numbers of CD8 + or PD-1 + TILs in tumor cells and the immune microenvironment of PCNS-DLBCL and analyzed their clinicopathological and prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of responses in some of these patients perhaps should be made with some caution, however, given the fact that 2 received whole-brain or focal irradiation immediately prior to nivolumab. 35 Nevertheless, these promising data, plus evidence that increased PDL-1/PD-1 expression in PCNSL may be associated with adverse prognosis, 36 constitute the basis for a multicenter phase 2 study of nivolumab in recurrent refractory PCNSL and PTL (NCT02857426).…”
Section: The Potential Of Novel Agents In Cns Lymphomasmentioning
confidence: 99%
“…1 Moreover, a recent report describes a higher incidence of neoplastic PD-L1 overexpression in primary DLBCL of the CNS (PCNS-DLBCL) compared to systemic ordinal cases. 12 This suggests that PD-L1 expression in tumor cells may play an important role in PCNS-DLBCL pathogenesis.…”
Section: Introductionmentioning
confidence: 99%